2017
DOI: 10.1038/s41598-017-16836-x
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide enhances the specificity of the polymerase chain reaction by modifying primer-template matching

Abstract: Aiming at improved specificity, nanoparticle assisted polymerase chain reaction (PCR) has been widely studied and shown to improve PCR. However, the reliability and mechanism of this method are still controversial. Here, we demonstrated that 1 μg/mL of graphene oxide (GO) effectively enhances the specificity of the error-prone multi-round PCR. Mismatched primers were designed as interference to produce nonspecific products when the same amounts of matched and mismatched primers were added into semi-multiplex P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…2). Although previous studies have demonstrated that GO can act as an efficient assistant additive to eliminate non-specific amplification [10,14], our study provides the quantitative data on microbial community level to prove the negative effect of GO. On the other hand, these observations are based on our mock communities.…”
Section: Effect Of Go On Pcr Amplification and Microbial Communitymentioning
confidence: 86%
See 2 more Smart Citations
“…2). Although previous studies have demonstrated that GO can act as an efficient assistant additive to eliminate non-specific amplification [10,14], our study provides the quantitative data on microbial community level to prove the negative effect of GO. On the other hand, these observations are based on our mock communities.…”
Section: Effect Of Go On Pcr Amplification and Microbial Communitymentioning
confidence: 86%
“…The effect of GO on DNA may be more complicated than expected Previous studies have proved that GO can eliminate non-specific amplification effectively [14,15]. However, their conclusions and proposed mechanisms lack quantitative data at the community level.…”
Section: Effect Of Go On Pcr Amplification and Microbial Communitymentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to release small RNAs bound to GO surface for further PCR/sequencing analysis. Indeed, at the critical concentration of 4 µg/ml, PCR reactions are inhibited by the GO in solution (Wang et al, 2017). The desorption of NAs from GO is indeed a complex problem (Liu et al, 2016).…”
Section: Small Mirnas Are Selectively Desorbed After the Increase Of mentioning
confidence: 99%
“…The PCR procedures are shown in Supplementary Table S1. After 25 cycles, ten microliter PCR products were subjected to 1% agarose gel electrophoresis (120 V/20 min), as described 57 .…”
Section: Identification Of P Aeruginosa By Endpoint Polymer Chain Rementioning
confidence: 99%